Does health education prevent childhood accidents? - Minchom, P. E. (BMJ Group, 1984)
In an attempt to test the assumption that health education directed at parents and children can reduce childhood accidents, a controlled study was carried out in Ely , one area of Cardiff. Using conventional health education techniques, the campaign was carried out in June and July 1981 and monitored by the numbers of injured children attending the local Accident and Emergency Department. Comparison of accident numbers in Ely between 1980 and 1981 and between Ely and the whole of Cardiff in 1981 showed no significant change. A slight increase in trivial injuries suggested an increased willingness to attend hospital. There was no change in the age distribution of victims. The benefits of health education and alternative methods of accident prevention are discussed and the need for further research is emphasized.